Get up and Get Moving: a nutrition and physical activity after-school program for Latino adolescents of Erie Neighborhood House. Issue 1 (2nd January 2022) - Akufo, Jennifer K.
Abstract: Obesity among Latino children in the United States is a serious health concern that poses a risk to develop other chronic illnesses such as Type 2 Diabetes, cancer, and heart disease. The following paper is focused on a 6-week health education intervention that was developed for 12- to 14-year-old Latino youth of an after -school program at a social service agency in the West Town neighborhood of Chicago. Within Chicago, childhood obesity rates in children of all ages were shown to be the second highest among Latino communities for both boys and girls. Implications from this article will provide insight into the need for public health professionals to further research and use that information to formulate ideas to create nutrition and physical activity programs that will address obesity among Latino and other ethnic youth populations—to promote and encourage them to adopt and maintain a healthy lifestyle.